Integrated approach in the assessment of skin compatibility of cosmetic formulations with green coffee oil. (16th April 2015) - Wagemaker, T. A. L.; Rijo, P.; Rodrigues, L. M.; Maia Campos, P. M. B. G.; Fernandes, A. S.; Rosado, C.
Abstract Objective Green coffee oil (GCO) has been used in cosmetic formulations due to its emollient and anti‐ageing properties. However, there are insufficient studies about its safety when applied in cosmetic formulations. Methods Cytotoxicity of GCO and of formulations containing 2.5–15% of GCO was evaluated by the MTT reduction assay, in human keratinocytes. Formulations containing 15% of GCO and the vehicle were applied under in use conditions in the volar forearm of human volunteers during 3 days. Transepidermal water loss, stratum corneum water content and erythema index were evaluated each 24 h using biophysical techniques. The same formulations were probed for skin tolerance through a patch test. Results Neither pure GCO nor its formulations showed cytotoxic effects in concentrations up to 100 μg mL−1. Transepidermal water loss values showed a slight reduction when the formulation containing GCO was applied. Stratum corneum water content and erythema index did not show significant differences, as the results observed in the first day of the study were maintained throughout 3 days. None of the volunteers display any reaction after using an occlusive patch. Conclusion The results obtained in the study indicate that GCO seems to be safe for topical applications and showed good skin compatibility under the experimental conditions of the study.